Elevated blood pressure in childhood and hypertension risk in adulthood: a systematic review and meta-analysis. Issue 12 (December 2020) - Yang, Lili; Sun, Jiahong; Zhao, Min; Liang, Yajun; Bovet, Pascal; Xi, Bo
Abstract : Objective: Several longitudinal studies have investigated the association between elevated blood pressure (BP) in childhood and hypertension in adulthood but the strength of the association has not been always consistent. This study aimed at quantitatively assessing the strength of the association between elevated BP in childhood and hypertension in adulthood based on both a meta-analysis and a systematic review. Methods: We identified eligible studies using PubMed and Embase databases up to 1 November, 2019 and by manually searching the reference lists of all identified studies. All longitudinal studies on the association between elevated BP in childhood and hypertension in adulthood were included. Summary odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using a random-effects model in this meta-analysis. Results: Eleven articles ( N  = 39 714) were included in our meta-analysis and five additional articles were used for systematic review (two providing ORs without 95% CIs, one not using standard cut-offs for elevated BP in childhood, and two not using standard criteria for adult hypertension). Elevated BP in childhood (3--18 years in the included studies) was significantly associated with hypertension in adulthood (18--57 years in the included studies), with a summary OR of 2.02 (95% CI 1.62--2.53). We also found that an increase of 1 standard deviation in systolic BP and diastolic BP, respectively, in childhood (3--19 years in the included studies) was associated with hypertension in adulthood (21--49 years in the included studies), with summary ORs of 1.71 (1.50–1.95) and 1.57 (1.37–1.81). Our systematic review of the five additional articles not eligible for meta-analysis also suggested a significant association between elevated BP in childhood and hypertension in adulthood. Conclusion: This meta-analysis and systematic review demonstrated a significant association between elevated BP in childhood and hypertension in adulthood. The findings support measures to promote healthy BP during childhood to reduce the risk of hypertension later in life. Abstract : Supplemental Digital Content is available in the text